Pemanfaatan media Sosial instagram Dalam Pemasaran UMKM Roti Al Batsit Kota Bengkulu - Susena, Karona Cahya; Refsi, Refsi Roziana (Jurnal Kewirausahaan dan Bisnis, 2023)
UMKM Roti Al Batsit is a small business engaged in the food industry which is located in the city of Bengkulu. As one of the MSMEs, the challenge that must be faced is how to increase product sales and introduce the Roti Al Batsit brand to the public. Therefore, a community service program with the title "Utilization of Instagram social media in Marketing of UMKM Bread Al Batsit Bengkulu City". The use of Instagram social media is done so that consumers can easily recognize and remember the Roti Al Batsit brand and give a positive image to the brand. During the implementation of the community service program, an evaluation of the impact of the program was carried out on the UMKM Roti Al Batsit. The evaluation is carried out by comparing product sales before and after the program is implemented. The evaluation results show that implementing the use of Instagram social media in proper marketing has succeeded in increasing the number of product sales in the community.